Relative Permittivity of Olive Oil for Electrical Purpose - Moses, Magdelene; Bahari, Azlina (Progress in Engineering Application and Technology, 2024)
This project investigates the electrical characteristics of two prominent variants of olive oil, normal olive oil, and virgin olive oil, with a primary focus on discerning their relative permittivity or dielectric constant. The imperative to identify sustainable alternatives to traditional dielectric materials, prompted by environmental concerns and heightened disposal expenses, underscores the significance of this study. The meticulous experimental journey involves a systematic approach, commencing with the precise collection of oil samples. Rigorous calibration of measuring instruments follows, ensuring accuracy and reliability in capturing capacitance readings.The experimental setup orchestrates a sequence of measurements, capturing capacitance values both before and after subjecting the oils to a controlled heating process. Subsequent to data acquisition, an in-depth analysis unfolds, revealing nuanced patterns and variations in the relative permittivity of normal and virgin olive oils. Beyond contributing to the fundamental understanding of olive oil’s dielectric properties, this project holds implications for a spectrum of applications. Ranging from food science to industrial processing and electrical engineering, the derived insights offer a multidimensional perspective on the potential utility of olive oils in diverse technological domains.In the backdrop of contemporary efforts to identify eco-friendly alternatives, the findings from this study pave the way for sustainable dielectric materials. The intersection of scientific exploration and practical applications positions this research at the forefront of endeavors to foster environmentally conscious technological advancements.